Road Widening and Land Use Land Cover Change Detection at Anantnag, Kashmir Road Widening and Land Use Land Cover Change Detection at Anantnag, Kashmir (International Journal of Innovative Research in Engineering & Management, 2023)
Road networks play a crucial role in  fostering economic growth and development. This current  research focuses on examining and identifying changes in  land use and land cover at a small scale. The study utilizes  a GIS-based approach, analyzing Landsat imagery taken  before (2019) and after (2022) a road widening project.  The results reveal a dynamic transformation in land use  and land cover in Anantnag, Kashmir, as a consequence of  the road widening. This includes the introduction of new  land use categories and significant alterations in the overall  land use pattern in the area.
Keywords: Road widening; land use land cover; change detection; Anantnag; Kashmir